PENGARUH KEPUASAN KERJA DAN PENDIDIKAN PELATIHAN TERHADAP PRESTASI KERJA SERTA DAMPAKNYA PADA MOTIVASI KARYAWAN PUSAT PENELITIAN PERKEBUNAN KARET SEMBAWA - Sulistari, Sulistari (LPPM Universitas Multi Data Palembang, 2025)
Abstract : This study aims to determine the effect of work discipline and training education on the motivation and its implication for the performance of employee in the Pusat Penelitian Perkebunan Karet Sembawa. In this study the total population was 60 people as study sample. Sampling in this study used saturated sampling techniques, namely sampling carried out as a whole from the population. Keywords : Work discipline, training education, motivation, performance.